Genetic privacy: orthodoxy or oxymoron?. Issue 2 (1st April 1999) - Sommerville, A; English, V
Abstract : In this paper we question whether the concept of "genetic privacy" is a contradiction in terms. And, if so, whether the implications of such a conclusion, inevitably impact on how society comes to perceive privacy and responsibility generally. Current law and ethical discourse place a high value on self-determination and the rights of individuals. In the medical sphere, the recognition of patient "rights" has resulted in health professionals being given clear duties of candour and frankness. Dilemmas arise, however, when patients decline to know relevant information or, knowing it, refuse to share it with others who may also need to know. This paper considers the notions of interconnectedness and responsibility to others which are brought to the fore in the genetic sphere and which challenge the primacy afforded to personal autonomy. It also explores the extent to which an individual's perceived moral obligations can or should be enforced.